Evaluation of heavy metal pollution in groundwater resources of Konaro area, Iranshahr, SE Iran: implication for ophiolitic rocks impact - Barahouei, Baseer Ahmad; Noura, Mohammad Reza; Moslempour, Mohammad Elyas; Dabiri, Rahim (Journal of Environmental Engineering and Landscape Management, 2025)
This study, it has been attempted to investigate the heavy metals pollution in groundwater resources of Konaro area. Accordingly, eight representative groundwater samples from wells and qanat were collected in December 2017 from rural settlements commonly used for irrigation and drinking. Analysis of lead, zinc, iron, chromium, copper and nickel as heavy metals was conducted by the ICP-MS approach. The results of analyzes indicate that the concentration of heavy metals in the groundwater of the study area is lower than the permissible limit. Results of HEI, HPI, and Cd contamination indices show that 62.5% of samples in the Konaro area fall into the medium pollution group, and the rest of the samples fall into the low pollution group due to their heavy metals content. Studies show that all samples of groundwater in the Konaro area have low to moderate contamination and that the overall contamination rate is not dangerous. Correlations between heavy metals indicators demonstrate that HPI is strongly correlated with HEI and Cd also HEI with Cd. Therefore, it is evident that all of the indices are important and reliable to study the risk of heavy metals pollution in the Konaro ophiolitic area. Pollution evaluation indices and statistical analysis confirm that the low to medium level of heavy metals in Konaro groundwater samples is owing to the lack of acidity, poor agriculture and poor urbanization around the river and thus the lack of contamination of the aquifer.